STUDY OF CONTACT FATIGUE STRENGTH FOR ISOTROPIC BARREL FINISHING GEAR - ZHAO GuangHui; LIU ShiJun; LI JiQiang; XU WenBo; LIU Jie; WANG XiaoPeng (Jixie qiangdu, 2017)
The surface roughness of traditional grinding gear has the typical anisotropy characteristic in microcosmic direction. After the barrel finishing of the tooth surface,the micro-surface is isotropic. According to the Hertz theory and the theory of contact fractal strength of gears,the influence of microstructure contact stress calculation was discussed. The contact stress limit of the traditional grinding gear and the barrel finishing gear was obtained by gear contact fatigue strength comparison test. The results show that the isotropic finishing process can make the micro-texture of the tooth surface tend to be isotropic,and improve the contact fatigue strength of the gears,which provides a reference for the life design and reliability design of the gear.